Karyotype analysis of Kutsay. Allium odoratum L. (Alliales Alliaceae). - Bermejo, Jo-Am Asis (1995.)
The C-metaphase count of Allium odoratum revealed that the chromosme number was 2n=32, consisting of the following centromeric groups based on Levan's method of chromosome classification: Group I chromosomes with subterminal centromeres (1pair); Group II with submedian centromeres (2pairs); and Group III with median centromeres (13pairs). The mean total lenghts of chromosome ranged from 8.534 0.054-16.624 0.600 u. Mitotic index for the species was found to be 10.87.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Kutsay; Allium odoratum L